2022
DOI: 10.1136/bmjopen-2021-056798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family presence during cardiopulmonary resuscitation on team performance and perceived task load: a prospective randomised simulator-based trial

Abstract: ObjectivesGuidelines recommend family presence to be offered during cardiopulmonary resuscitation (CPR). Data on the effects of family presence on the quality of CPR and rescuers’ workload and stress levels are sparse and conflicting. This randomised trial investigated the effects of family presence on quality of CPR, and rescuers’ perceived stress.DesignProspective randomised single-blind trial.SettingVoluntary workshops of educational courses.Participants1085 physicians (565 men) randomised to 325 teams ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Almost two-thirds of the participants (65%) revealed that the presence of family would negatively affect the performance of the resuscitation team. In reality, it was discovered that the attitudes of healthcare professionals varied greatly with between 15-85% in favor of FPDR [21]. The difference between the present study and that conducted by Al-Mutair et al could be attributed to variation in the demographic characteristics of the participants; we included consultants, the majority of whom were men whereas the Al-Mutair study included nurses, mostly women.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Almost two-thirds of the participants (65%) revealed that the presence of family would negatively affect the performance of the resuscitation team. In reality, it was discovered that the attitudes of healthcare professionals varied greatly with between 15-85% in favor of FPDR [21]. The difference between the present study and that conducted by Al-Mutair et al could be attributed to variation in the demographic characteristics of the participants; we included consultants, the majority of whom were men whereas the Al-Mutair study included nurses, mostly women.…”
Section: Discussionmentioning
confidence: 60%
“…The research also discovered that while there was no apparent detrimental impact on the standard of CPR, FPDR was linked to an increase in frustration and perceived temporal and mental demands [20]. Another recent study revealed that, especially in pediatric situations, parents and family members desire the opportunity to be present [21].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that FPDR does not affect adult resuscitation outcomes 59 or increase stress levels of HCP during FPDR 60,61 . However, simulation studies of student nurses and physicians indicate that FPDR may negatively impact the quality of acute medical care 41,42,59 . In a simulation study with paramedics, it was observed that the presence of socioemotional stress, in this case from the presence of an upset friend, increased the subjective workload and frustration of HCP 62 .…”
Section: Discussionmentioning
confidence: 97%
“…Elevated stress levels may impede performance on tasks which requires divided attention, working memory, retrieval of information from memory, and decision making 58 . It seems that FPDR does not affect adult resuscitation outcomes 59 or increase stress levels of HCP during FPDR 60,61 . However, simulation studies of student nurses and physicians indicate that FPDR may negatively impact the quality of acute medical care 41,42,59 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a prospective comparative trial of two cohorts: during the pandemic years 2020 and 2021, all participants of our workshops performed CPR with PPE (PPE group), while a cohort of participants of pre-pandemic workshops of 2016 to 2019 [ 23 , 24 , 25 ] served as the control group. Apart from the need to wear PPE, the conditions and settings for both cohorts were identical.…”
Section: Methodsmentioning
confidence: 99%